2021
DOI: 10.4149/km_2014_2_99
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, properties and welding of T24 steel – critical review

Abstract: In this paper a new bainitic 7CrMoVTiB10-10 (T24) steel has been described on the basis of our own research results and a review of relevant literature. The T24 creep-resistant steel is known to be intended for membrane walls in power-generation units operating at supercritical steam parameters. Chemical composition, thermal treatment, microstructure and mechanical properties of T24 steel were characterized. Moreover, the processes of microstructure degradation during ageing/creeping and their effects on mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
2
19
0
1
Order By: Relevance
“…Microstructural evolution and mechanical properties of T24 steels during long-term ageing and/or creep exposure have been widely studied by many authors [10][11][12][13][14][15][16]. These studies revealed precipitation of several secondary phases in T24 base materials and their welded joints such as MX, M 2 C, M 6 C, M 7 C 3 , and M 23 C 6 , where M stands for various metallic elements, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microstructural evolution and mechanical properties of T24 steels during long-term ageing and/or creep exposure have been widely studied by many authors [10][11][12][13][14][15][16]. These studies revealed precipitation of several secondary phases in T24 base materials and their welded joints such as MX, M 2 C, M 6 C, M 7 C 3 , and M 23 C 6 , where M stands for various metallic elements, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…V, Nb, Ti in MX; Mo in M 2 C and M 6 C; and Cr in M 7 C 3 and M 23 C 6 ; X = C, N). Moreover, it has been found out that long-term thermal exposure of T24 material leads to privileged carbide precipitation on grain boundaries, additional precipitation of M 2 C carbides, the enriching of MX carbonitrides with molybdenum and recovery processes of tempered bainitic microstructure [10]. The T92 steel is a 9Cr-0.5Mo-1.8W base tempered martensitic steel with minor additions of V, Nb, and B, developed during the late 1990s through chemical composition modification of T91 (9Cr-1Mo base) steel, aimed for the improvement of high temperature creep strength [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is the continuous introduction of new materials such as advanced automotive steels, galvanized high-strength dual-phase steel, trip steels, increase use of aluminium and composites, "sandwich" steel, and tailored blanks [2][3][4]. The conventional resistance and arc welding methods are not proper for welding of new materials and joints of dissimilar materials [38][39][40][41][42]. Therefore, the laser welding is increasingly used in the automotive industry [1,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty in welding various kinds of steel contribute to the formation of cracks both during the welding process and after its completion, or in the course of the heat treatment [1][2][3][4][5]. Selective heating of joined materials to the melting temperature of the materials during welding followed by crystallization and cooling of the weld cause the stresses and deformations in the area of the joint [6][7][8][9][10][11][12][19][20]. Cracks may also be a result of a prolonged operation of the system subjected to a high temperature of the flowing medium and vibrations [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%